(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Based on Max Weber’s sociological viewpoint, the idea of value-free science stresses keeping a researcher’s personal beliefs apart from their scientific investigation. This study looks at the continuous debate between value-laden science and the ideal of no values, especially in the domains of economics and management. Although objectivity is still a primary goal in scientific work, the research discovers through a qualitative literature review and bibliometric analysis using VOSviewer with Scopus data that values—ethical, social, and cultural—inevitably influence different stages of research, from topic selection to methodology and interpretation. Since organisational interests and underlying values frequently influence decision-making processes, the idea of neutrality in management is coming under increasing pressure. This study calls for a more thoughtful and morally responsible approach to research and organisational practice, highlighting the growing awareness among academics of the unavoidable presence of values in science.